2000
DOI: 10.1177/096120330000900711
|View full text |Cite
|
Sign up to set email alerts
|

Increased cervical dysplasia in intravenous cyclophosphamidetreated patients with SLE: a preliminary study

Abstract: To determine if intravenous cyclophosphamide (IV-C) causes an excess of cervical dysplasia and/or cancer in systemic lupus erythematosus (SLE) patients, a retrospective review was conducted. Patients with SLE who received IV-C between 1988-98 (study group) were compared with a group of SLE patients who had not received IV-C (control group). Of the 79 IV-C-treated SLE patients identified, we excluded 18 because of absence of pertinent data. We found 10 cases of cervical dysplasia in the remaining 61 patients, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 11 publications
3
47
0
1
Order By: Relevance
“…1,2 Further, in studies with systemic lupus erythematosus, a disorder in which immunosuppressive medications are commonly used long-term, there is evidence suggesting that exposure to immunosuppressants increases the risk of an abnormal Papanicolaou (Pap) test. [3][4][5] Similar results have been found in immunosuppressed transplant and cancer patients. 6 -10 Current recommendations published by the American College of Obstetricians and Gynecologists (ACOG) suggest yearly cytological screening for women younger than 30, and screenings every 2-3 years for older women who have 3 consecutive negative Pap smears.…”
supporting
confidence: 88%
“…1,2 Further, in studies with systemic lupus erythematosus, a disorder in which immunosuppressive medications are commonly used long-term, there is evidence suggesting that exposure to immunosuppressants increases the risk of an abnormal Papanicolaou (Pap) test. [3][4][5] Similar results have been found in immunosuppressed transplant and cancer patients. 6 -10 Current recommendations published by the American College of Obstetricians and Gynecologists (ACOG) suggest yearly cytological screening for women younger than 30, and screenings every 2-3 years for older women who have 3 consecutive negative Pap smears.…”
supporting
confidence: 88%
“…Venereal warts are caused by human papillomavirus (HPV), an agent also associated with cervical malignancy. A predisposition to HPV infection may explain some of the increased incidence of cervical atypia reported in SLE [48,49]. Another agent of interest is the Epstein-Barr virus (EBV), a known agent in the malignant transformation of lymphocytes [50], which has also been implicated in the pathogenesis of SLE [51,52].…”
Section: Infectionsmentioning
confidence: 99%
“…10 In contrast, the ®ndings by Cibere and colleagues are consistent with other studies in providing support for an association between SLE and lymphoproliferative disorders. 10 SLE and cancer, notably lymphoproliferative 10 ± 21 (personal communication Dr G Sturfelt and Dr O Nived), cervical (including dysplasia), 10,22,26 and breast, 27 have been described in a variety of case reports, 13 Despite numerous case reports and case and clinical series documenting the occurrence of malignancy in SLE, it is only through cohort studies comparing the observed number of cancers with those expected that the hypothesis of a positive association between SLE and malignancy can be evaluated. However, as shown in Table 1, the results from the cohort studies regarding cancer risk are not in agreement and none have suf®cient numbers to comment de®nitively on the potential risk factors such as immunosuppressive drug use in these patients.…”
mentioning
confidence: 99%